S62798, a potent TAFIa inhibitor, accelerates endogenous fibrinolysis in a murine model of pulmonary thromboembolism. Issue 204 (August 2021) - Sansilvestri-Morel, Patricia; Rupin, Alain; Schaffner, Arnaud-Pierre; Bertin, Florence; Mennecier, Philippe; Lapret, Isabelle; Declerck, Paul J.; Baumy, Philippe; Vallez, Marie-Odile; Petit-Dop, Florence; Tupinon-Mathieu, Isabelle; Delerive, Philippe
Abstract: Enhancement of fibrinolysis constitutes a promising approach to treat thrombotic diseases. Venous thrombosis and thromboembolism risks are associated with increased plasma levels of TAFI (Thrombin Activatable Fibrinolysis Inhibitor) as well as its active form TAFIa. A new TAFIa inhibitor, namely S62798 has been identified. Its ability to enhance fibrinolysis was investigated both in vitro and in vivo in a mouse model of pulmonary thromboembolism, as well as its effect on bleeding. S62798 is a highly selective human, mouse and rat TAFIa inhibitor (IC50 = 11; 270; 178 nmol/L, respectively). It accelerates lysis of a human clot in vitro, evaluated by thromboelastometry (EC50 = 27 nmol/L). In a rat tail bleeding model, no effect of S62798 treatment was observed up to 20 mg/kg. Enhancement of endogenous fibrinolysis by S62798 was investigated in a mouse model of Tissue Factor-induced pulmonary thromboembolism. Intravenous administration of S62798 decreased pulmonary fibrin clots with a minimal effective dose of 0.03 mg/kg. Finally, effect of S62798 in combination with heparin was evaluated. When treatment of heparin was done in a curative setting, no effect was observed whereas a significantly decreased pulmonary fibrin deposition was observed in response to S62798 alone or in combination with heparin. This study demonstrates that S62798 is a potent TAFIa inhibitor with minimal risk of bleeding. In vivo, curative S62798 intravenous treatment, alone or associated with heparin, accelerated clot lysis by potentiating endogenous fibrinolysis and thus decreased pulmonary fibrin clots. S62798 is expected to be a therapeutic option for pulmonary embolism patients on top of anticoagulants. Highlights: Venous thrombosis is associated with increased activity of fibrinolysis inhibitors. Inhibition of TAFIa improves endogenous fibrinolysis. TAFIa inhibition has no impact on bleeding. TAFIa inhibition accelerates in vivo thrombus lysis.